(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
Proverbs and sayings are two types of traditional expressions that have been used for centuries to convey wisdom, advice, and cultural norms. Both proverbs and sayings are typically short, easy-to-remember phrases that are used to make a point or to illustrate a truth. However, there are also some key differences between the two types of expressions. This study examined the differences and similarities between proverbs and sayings using a corpus of 100 proverbs and sayings. The study found that proverbs and sayings share a number of similarities. Both types of expressions are typically short, easy-to-remember phrases that are used to make a point or to illustrate a truth. Proverbs and sayings also often use figurative language, such as metaphors and similes.